A Proposal of Radio Ultrawideband Systems for Precision Indoor Localization - Jeřábek Jakub; Zaplatílek Luděk; Pola Marek (IEEE (Institute of Electrical and Electronics Engineers), 2015)
Indoor localization systems have been used in many divers application of commercial, public service and military sectors. This paper presents a proposal of system for ultra-wideband (UWB) radio system allowing Real Time Localization (RLTS) in indoor environment. Accurately tracking people in indoor locations is a very difficult technical problem that has not yet been completely solved. UWB transmission technology is primary attractive in GPS denied environments such as buildings. In this paper will be described important parameters of ultra-wideband radio system that depends on complicated conditions especially in buildings. Another goal of this paper is to examine the basic positioning principle and various approach of realizations of UWB systems which would be used for tracking people in complex indoor environments. This application has been recently researched in many scientific papers and experimentally studied. The UWB localization system is especially suitable in this context because it allows centimeters accuracy in ranging, as well as low-power and low-cost implementation.
Návrh širokopásmového rádiového sytému pro přesnou lokalizaci v budově
Keywords: Indoor positioning; OFDM; RLTS; UWB; UWB; OFDM; RTLS